Maternal engineered nanomaterial inhalation during gestation alters the fetal transcriptome - P. A. Stapleton (Particle and Fibre Toxicology, 2018)
Abstract Background The integration of engineered nanomaterials (ENM) is well-established and widespread in clinical, commercial, and domestic applications. Cardiovascular dysfunctions have been reported in adult populations after exposure to a variety of ENM. As the diversity of these exposures continues to increase, the fetal ramifications of maternal exposures have yet to be determined. We, and others, have explored the consequences of ENM inhalation during gestation and identified many cardiovascular and metabolic outcomes in the F1 generation. The purpose of these studies was to identify genetic alterations in the F1 generation of Sprague-Dawley rats that result from maternal ENM inhalation during gestation. Pregnant dams were exposed to nano-titanium dioxide (nano-TiO2) aerosols (10 ± 0.5 mg/m3) for 7-8 days (calculated, cumulative lung deposition = 217 ± 1 μg) and on GD (gestational day) 20 fetal hearts were isolated. DNA was extracted and immunoprecipitated with modified chromatin marks histone 3 lysine 4 tri-methylation (H3K4me3) and histone 3 lysine 27 tri-methylation (H3K27me3). Following chromatin immunoprecipitation (ChIP), DNA fragments were sequenced. RNA from fetal hearts was purified and prepared for RNA sequencing and transcriptomic analysis. Ingenuity Pathway Analysis (IPA) was then used to identify pathways most modified by gestational ENM exposure. Results The results of the sequencing experiments provide initial evidence that significant epigenetic and transcriptomic changes occur in the cardiac tissue of maternal nano-TiO2 exposed progeny. The most notable alterations in major biologic systems included immune adaptation and organismal growth. Changes in normal physiology were linked with other tissues, including liver and kidneys. Conclusions These results are the first evidence that maternal ENM inhalation impacts the fetal epigenome.